2020
DOI: 10.1017/ice.2020.334
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 51-hospital Chicagoland regional antibiogram and comparison to local hospital and national surveillance data

Abstract: Objective: To develop a regional antibiogram within the Chicagoland metropolitan area and to compare regional susceptibilities against individual hospitals within the area and national surveillance data. Design: Multicenter retrospective analysis of antimicrobial susceptibility data from 2017 and comparison to local institutions and national surveillance data. Setting and participants: The analysis included 51 hospitals from the Chicago–Naperville–Elgin Metropolitan Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…One of the most important tools available in assisting with risk stratification and the optimization of empiric antibacterial therapy are antibiograms. Antibiograms provide regionor country-level guidance for appropriate empiric therapy based on resistance patterns within the patient population of an institution, region, or country, but data may not be generalizable to specific patient populations or locations [10,11]. The Clinical and Laboratory Standards Institute M39 provides guidance to microbiology laboratories for the development of an antibiogram to ensure accuracy, reliability, and statistical validity [17].…”
Section: Antibiogramsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important tools available in assisting with risk stratification and the optimization of empiric antibacterial therapy are antibiograms. Antibiograms provide regionor country-level guidance for appropriate empiric therapy based on resistance patterns within the patient population of an institution, region, or country, but data may not be generalizable to specific patient populations or locations [10,11]. The Clinical and Laboratory Standards Institute M39 provides guidance to microbiology laboratories for the development of an antibiogram to ensure accuracy, reliability, and statistical validity [17].…”
Section: Antibiogramsmentioning
confidence: 99%
“…Fortunately, there are a variety of tools available to clinicians in assisting with early antimicrobial optimization, decreasing TTET, and improving outcomes such as mortality, length of stay, and costs. One such tool is the antibiogram, which has evolved in its complexity and utility from its traditional version into more modern forms capable of providing more accurate and usable antimicrobial susceptibility information [10,11]. Data from these antibiograms may assist clinicians in making more informed and timely antibacterial susceptibility testing requests for new antibacterial agents for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Prior publications have documented the feasibility of developing cumulative antibiograms at the regional and state levels. [9][10][11] These studies recognize the difficulties associated with combining antibiograms from multiple facilities, including formatting issues, adherence to Clinical Laboratory and Standards Institute (CLSI) guidelines, variation in hospital size and case mix, and isolate testing methods. 1,12 Prior studies combining antibiograms in regions or communities have shown differences from other external-facing surveillance programs such as SENTRY, but have not investigated the clinical utility these tools might have.…”
Section: Introductionmentioning
confidence: 99%
“…1,12 Prior studies combining antibiograms in regions or communities have shown differences from other external-facing surveillance programs such as SENTRY, but have not investigated the clinical utility these tools might have. 11 We sought to not only create a combined antibiogram for our community but also to find ways to disseminate the data to local providers.…”
Section: Introductionmentioning
confidence: 99%
“…7 – 9 Regardless of these limitations, cumulative antibiograms have previously been validated to have meaningful results for communities. 8 , 10 , 11 They are a practical and inexpensive tool to aid clinicians in empiric antimicrobial choices, and with significant clinical significance. 5 , 6 , 10 …”
mentioning
confidence: 99%